Vpliv postavitve rok na porazdelitev sil med nogama pri nordijskem spustu zadnje lože – pilotna študija - Spudić, Darjan (Šport (Ljubljana), 2022)
The Nordic hamstring exercise is commonly used in training to increase the eccentric strength of the hamstrings and consequently to improve physical abilities and reduce the risk of hamstring injuries. Changing the inclination of the lower leg support and the position of the ankle (i.e., plantar or dorsiflexion) has been shown to affect the observed mechanical variables during the Nordic hamstring strength test. No previous study has examined the effect of different hand positions on the distribution of load between the legs. Therefore, the aim of our study was to investigate the effects of upper extremity position (hands behind the back, right arm extended, and left arm extended) on the maximal knee torque generated during the Nordic hamstring test. In the future, the exercise variation could serve as a practical alternative to increase the eccentric strength of the hamstrings and simultaneously reducing asymmetries in eccentric strength between the hamstrings. As a result, this could improve the physical abilities of athletes while reducing the risk of hamstring injuries. A cross-sectional study was conducted including Faculty of Sport students. It was found that left leg torque and symmetry index values did not differ between the three exercise variations. The only differences were found in the results for the right leg, where differences were found between the variants with the hands behind the back and the left arm extended, and between the variants with left arm extended and the right arm extended. In conclusion, the position of the upper extremities has a negligible effect on the distribution of torque between the legs during the execution of the Nordic hamstring exercise. Future research in this area must aim to find more optimal variations of the exercise with an improved and more in-depth methodological approach.
Keywords: asimetrija; moč; navor; nordijska vaja; nordijski spust; nordijski upogib; šport